2013
DOI: 10.4103/0972-124x.115657
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of levels of C-reactive protein and PMN in periodontitis patients related to cardiovascular disease

Abstract: Background:Numerous cross-sectional studies have suggested that chronic periodontitis is a risk factor for cardiovascular diseases. There is evidence that periodontitis and cardiovascular diseases are linked by inflammatory factors including C-reactive protein. The purpose of the study was to investigate the levels of CRP and PNM cells as a marker of inflammatory host response in the serum of chronic periodontitis patients and in patients with CVD.Materials and Methods:Study population included 75 patients; bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
(15 reference statements)
1
9
0
Order By: Relevance
“…Periodontitis and CVD are strongly associated and they potentially share many risk factors like stress, smoking, diet, lack of physical exercise, obesity and atherosclerotic lesions 5 ; they share a common pathogenetic process like monocyte hyper responsiveness, formation of atheromas (atherosclerosis) and rise in systemic levels in CRP. 1,10 Moreover the CRP levels were increased in the chronic periodontitis patients with CVD when compared to chronic periodontitis patients without CVD or controls, our results were consistent with studies conducted by Malhotra S 1 , Anitha G et al 5 , Tuter G et al 16 , Glurich et al 17 , and Loesche 18 who found a positive correlation between the CRP levels in periodontitis patients with CVD. In addition it has certain limitations.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Periodontitis and CVD are strongly associated and they potentially share many risk factors like stress, smoking, diet, lack of physical exercise, obesity and atherosclerotic lesions 5 ; they share a common pathogenetic process like monocyte hyper responsiveness, formation of atheromas (atherosclerosis) and rise in systemic levels in CRP. 1,10 Moreover the CRP levels were increased in the chronic periodontitis patients with CVD when compared to chronic periodontitis patients without CVD or controls, our results were consistent with studies conducted by Malhotra S 1 , Anitha G et al 5 , Tuter G et al 16 , Glurich et al 17 , and Loesche 18 who found a positive correlation between the CRP levels in periodontitis patients with CVD. In addition it has certain limitations.…”
Section: Discussionsupporting
confidence: 89%
“…But chronic periodontitis show the rise of CRP levels in the blood, which is a risk indicator of cardiovascular disease. 5,6…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Periodontal disease is similarly associated with increased systemic inflammatory markers, including C-reactive protein and interleukin-6. [18][19][20] Thus, the association between periodontal disease and atherosclerosis presented in previous reports 19,20) may not be a direct relationship; however, it may be a reflection of the increased levels of inflammatory markers in both diseases. Our results showing the nonexistence of a strong correlation between periodontal condition and arteriosclerosis severity were consistent with the recent American Heart Association statement.…”
Section: Discussionmentioning
confidence: 97%
“…One study suggested that the concentration of serum neutrophil markers, myeloperoxidase (MPO) and high matrix metalloproteinase (MMP)-8/tissue inhibitor of metalloproteinase (TIMP)-1 ratio increased the risk of recurrent acute coronary syndrome (ACS) [10]. Most recently, neutrophils have been implicated as mediators in periodontitis-myocardial infarction studies [6,11]. However, the scientific studies in this area are scarce.…”
mentioning
confidence: 99%
“…In patients with stable coronary heart disease (CHD), a higher CRP concentration increases the risk of MI, whereas in patients with unstable CHD and MI history, it yields a worse prognosis and a higher risk of complications [5,6]. Even after taking into consideration other conventional risk factors, such as arterial hypertension or cholesterol level, CRP remains an independent predictor of coronary risk [7].…”
mentioning
confidence: 99%